ANALYSIS OF THE FACTORS CAUSING PROBLEMATIC FINANCING AT BANK SYARIAH INDONESIA MAGELANG SINGOSARI SUB-BRANCH OFFICE - Ahmad Arif Prasetya; Utpala Rani; Siti Afidatul Khotijah (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2022)
Indonesian Islamic banks are banks in Indonesia engaged in Islamic banking in financial institutions that meet the public's needs for financing transactions. Bank Syariah Indonesia Magelang Singosari Sub-Branch Office is having problems with financing. Factors that cause problematic financing come from internal factors and external factors. This research aims to find out what factors cause problematic funding at Indonesian Sharia banks, the Magelang Singosari Sub-Branch Office and to find out how to deal with ineffective financing at the Indonesian Sharia Bank, the Magelang Singosari Sub-Branch Office. This research method uses qualitative data types. The data in this study were collected and organized, and sorted in a certain pattern so that the data is determined and sorted according to the research discussion. The causes of unfavorable financial conditions are internal factors and external factors at Bank Syariah Indonesia Sub-Branch Office Magelang Singosari, internal factors the bank does not delve into in the analysis of prospective customers, external factors in particular 1) the possibility that the customer wants to pay before maturity but cannot pay it off due to a disaster the customer does not have the income to pay for the financing that is due 2) the intentional factor of the customer intentionally delaying payment of funds that are due.